2008
DOI: 10.1074/jbc.m709935200
|View full text |Cite
|
Sign up to set email alerts
|

Human Major Histocompatibility Complex (MHC) Class I Molecules with Disulfide Traps Secure Disease-related Antigenic Peptides and Exclude Competitor Peptides

Abstract: The ongoing discovery of disease-associated epitopes detected by CD8 T cells greatly facilitates peptide-based vaccine approaches and the construction of multimeric soluble recombinant proteins (e.g. tetramers) for isolation and enumeration of antigen-specific CD8 T cells. Related to these outcomes of epitope discovery is the recent demonstration that MHC class I/peptide complexes can be expressed as single chain trimers (SCTs) with peptide, ␤ 2 m and heavy chain connected by linkers to form a single polypepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…Bypassing the normal epitope processing requirements and increasing the rate of assembly of the class I molecule would be expected to increase significantly the steadystate level of presented peptide epitope at the cell surface, and hence increase the CD8 ϩ T cell response (22). A second potential advantage is that SCTs have increased cell surface stability, as compared with the equivalent wild-type MHC class I molecules (3,23). Recently, it has been shown that at equivalent levels of cell surface expression, antigenic peptide-MHC class I molecules with longer half-lives stimulate greater CD8 ϩ T cell responses (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bypassing the normal epitope processing requirements and increasing the rate of assembly of the class I molecule would be expected to increase significantly the steadystate level of presented peptide epitope at the cell surface, and hence increase the CD8 ϩ T cell response (22). A second potential advantage is that SCTs have increased cell surface stability, as compared with the equivalent wild-type MHC class I molecules (3,23). Recently, it has been shown that at equivalent levels of cell surface expression, antigenic peptide-MHC class I molecules with longer half-lives stimulate greater CD8 ϩ T cell responses (24).…”
Section: Discussionmentioning
confidence: 99%
“…1A), we have found that poorly immunogenic epitopes that have low binding affinities for class I fail to assemble efficiently as SCTs and are expressed poorly at the cell surface (K. Gould, unpublished results). However, recent ingenious improvements in SCT design by Hansen and colleagues, in particular the introduction of a disulfide trap to anchor the peptide epitope in the peptide binding groove of class I (23,28,29), offer the promise that even weakly binding peptide epitopes may be expressed as stable SCTs, and thereby improve their ability to stimulate CD8 ϩ T cell responses in vivo. This remains to be tested experimentally, but our results emphasize that such studies would be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the concept of antibody-mediated delivery of pMHCI complexes to tumor cells as a therapeutic approach was never tested with unstimulated human PBMCs (19,25,28) although most likely these cells would constitute the primary source of CD8 þ effector T cells. It was unclear, however, whether naturally observed frequencies of CMV-specific effector CD8 þ T cells were sufficient to mediate significant tumor cell killing.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a single virus-derived peptide is sufficient to attract a large number of T cells. The concept of mimicking a viral infection in cancer cells by targeting pMHCI complexes to their surface was proposed already several years ago (19,28). To date, various fusion molecules were designed for this purpose; basically all of them were produced as antibody fragments in bacteria (combined with refolding), followed in most cases by in vitro peptide-loading, chemical-conjugation, or T-cell group) or pMHCI-IgG constructs were administered at 50 mg/mouse ($2 mg/kg) beginning 6 hours after engraftment (day 0), after 24 hours (day 1), and then every 2 to 3 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation